2013
DOI: 10.1016/j.fob.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant 1‐deoxy‐d‐xylulose‐5‐phosphate synthase from Plasmodium vivax in Escherichia coli

Abstract: Humanity is burdened by malaria as millions are infected with this disease. Although advancements have been made in the treatment of malaria, optimism regarding our fight against malaria must be tempered against the problem of drug resistance in the Plasmodium parasites causing malaria. New targets are required to overcome the resistance problem. The enzymes of the mevalonate-independent pathway of isoprenoid biosynthesis are targets for the development of novel antimalarial drugs. One enzyme in this pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Overexpression of this metabolic branch point enzyme may have deleterious effects on metabolism. There is evidence that DXP synthase aggregates upon overexpression, 37,38,66 and its overexpression causes toxicity to bacterial cells. 3941,43,45,67 Despite this, we have successfully shown that basal expression of this enzyme confers resistance to some alkylAPs, albeit to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of this metabolic branch point enzyme may have deleterious effects on metabolism. There is evidence that DXP synthase aggregates upon overexpression, 37,38,66 and its overexpression causes toxicity to bacterial cells. 3941,43,45,67 Despite this, we have successfully shown that basal expression of this enzyme confers resistance to some alkylAPs, albeit to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The cloning of Pv DXS was described previously. [30] The cloning of Pf DXR has also been previously described, [31] and this gene was generously donated by Dr. Nobutada Tanaka at Showa University (Japan) for the use in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested by centrifugation, and the cell pellets stored at −80 °C. The expression of Pv DXS [30] and Pf DXR [31] were described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we describe the active site architecture of 1-deoxy-D-xylulose 5-phosphate synthase, a target for antimicrobial agents, herbicides, and antimalarial drugs [22] [23]. A role in catalysis has been assigned to conserved amino acid residues and a model of the catalytic site has been generated which can be of great interest to predict drug-enzyme interactions.…”
Section: Kinetic Studiesmentioning
confidence: 99%